PERANAN TERAPI INSULIN INTENSIF TERHADAP INTERLEUKIN-6 (IL-6) DAN LUARAN KLINIK PADA PENDERITA KRITIS DENGAN HIPERGLIKEMIA - Wiryana, Made (journal of internal medicine, 2008)
Hiperglycemia and insulin resistance are common in critically ill patients, even that have not previously had diabetes.Though it has been reported that pronounced hyperglycemia may lead to complications in such patients and cause of reactiveoxygen species (ROS) production, although data from controlled trial are still lacking. The debatable issue focused on whetherintensive insulin therapy to normalized blood glucose improves prognosis. The debate is mainly about the time to start therapy,and target of blood glucose level. The main purpose of this research is to know the different between intensive insulin therapy andconventional insulin therapy on decreases of cytokine production (IL-6), increase of albumin level and event of systemic inflammatoryrespons syndrome (SIRS). The design of this study is randomized pre and post control group design involving 40 adultpatients that admitted to the ICU Sanglah hospital Denpasar. They were randomly assigned to receive intensive insulin therapy inwhich blood glucose at the level between 80 ? 110 mg/dL or conventionl insulin therapy in which insulin therapy start if the bloodglucose level exceed 215 mg/dL and blood glucose maintained at the level between 180 ? 200 mg/dL. The results of this studyshowed that: (1) Significant decrease of IL-6 level (10.25 vs 2.02; p=0.023); (2) Significant increase of albumin level (0.62 vs0.22); (3) Significant decrease of SIRS (10 % vs 45%, p=0.000) on intensive insulin therapy group compare to the conventionalinsulin therapy group. Conclusions of this study is that the increase insulin dose as well as intensive insulin therapy can maintainblood glucose level at the level normoglycaemia between 80-110 mg/dL faster compare to the conventional insulin therapy. Onthe otherhand, interleukin-6 decreases cause of decreases ROS production and anti inflammatory effect of insulin. Intensiveinsulin therapy can increase albumin level and decrease of SIRS event on hyperglycemia in critically ill ICU patients compare tothe conventional insulin therapy.